Strategy for Developing Inter-Village Cooperation as an Effort to Increase Village Original Income (PADes) - Sutoyo, Andi; Tamtomo, Hario; Tri Kurniasih, Endah (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
Indonesia generally consists of rural areas with abundant natural resources and the potential to support national economic growth. However, the utilization of this potential is often hampered by limited management capacity and resources in each village. This study aims to examine strategies for developing inter-village collaboration to increase Village Original Income (PADes). The study was conducted in Mekar Sari Village, Muaro Jambi Regency, using qualitative methods through observation and in-depth interviews. The results indicate that inter-village collaboration in managing local economic potential, strengthened by institutions such as Village-Owned Enterprises (BUMDes) and participatory planning, is an effective strategy for increasing PADes. This strategy involves steps such as identifying potential, optimally allocating resources, and building coordination and communication among village stakeholders. Therefore, strengthening inter-village collaboration can be a means to achieve village financial independence and accelerate improvements in community welfare